Moving forward on choosing a standard operational indicator of women’s dietary diversity - Martin Prével, Y.; Allemand, P.; Wiesmann, D.; Arimond, M.; Ballard, T.; Deitchler, M.; Dop, M.C.; Kennedy, G.; Lee, W.T.K.; Moursi, M. (Food and Agriculture Organization of the United Nations, 2015)
Monotonous diets fail to meet human micronutrients' needs. Consequently, dietary diversity is crucial for vulnerable groups, in particular for women of reproductive age (WRA). Could the dietary diversity be measured and used as a simple population-level proxy indicator collected via large-scale surveys to reflect the micronutrient adequacy of WRA’s diets? In 2005-2010, results from the Women’s Dietary Diversity Project (WDDP) on the relationship between food group diversity and micronutrient adequacy of the diets of WRA did not lead to the development of a dichotomous indicator for use across all contexts. To address this need, FAO initiated in 2012 a follow-up project (WDDP II) aiming to a) identify additional datasets to analyse; b) explore if larger number of datasets strengthens evidence to inform the most appropriate food group composition to comprise the indicator; c) investigate whether a standard cut-off can be identified to formulate a valid dichotomous women’s dietary diversity indicator.